Rosencrantz & Guildenstern are dead [videorecording (DVD)] - Stoppard, Tom; Stoppard, Tom; Oldman, Gary; Roth, Tim; Dreyfuss, Richard (RLJ Entertainment, 2016)
In this cleverly inspired twist on William Shakespeare's Hamlet, two of the outrageous supporting players take center stage for a dazzling game of illusion and reality that delivers one-of-a-kind entertainment!